DOI: 10.11606/t.41.2012.tde-17072012-091307
|View full text |Cite
|
Sign up to set email alerts
|

Treponematoses e outras paleopatologias em sítios arqueológicos pré-históricos do litoral sul e sudeste do Brasil

Abstract: Treponematoses e outras paleopatologias em sítios arqueológicos pré-históricos do litoral sul e sudeste do Brasil (j.Filippini-2012) DEDICATÓRIA Quando nos acostumamos a ler as dedicatórias de teses acabam virando rotina as homenagens aos familiares pela compreensão e ajuda. Só mesmo ao se debruçar em um tipo de trabalho como este, extenso em tempo e conteúdo é que nos conscientizamos do porquê das dedicatórias insistirem tanto neste tipo de abordagem, que aqui repito. Muito obrigado à minha querida esposa Déb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
8

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
1
1
0
8
Order By: Relevance
“…Within our samples, it seems clear that women from the Atlantic coast had an abundance of iodine, fluorine, calcium, and possibly vitamin D, from having greater access to marine resources. This was confirmed by stable isotope studies and by the fact that extensive paleopathological studies have not found rickets in individuals from any of the sambaqui populations studied here . On the Pacific Coast, marine resources probably met some of those nutritional needs as the populations that lived nearby still consumed fish and molluscs, albeit on a smaller scale, considering that agricultural products had already become the significant source of food in this region .…”
Section: Discussionsupporting
confidence: 75%
“…Within our samples, it seems clear that women from the Atlantic coast had an abundance of iodine, fluorine, calcium, and possibly vitamin D, from having greater access to marine resources. This was confirmed by stable isotope studies and by the fact that extensive paleopathological studies have not found rickets in individuals from any of the sambaqui populations studied here . On the Pacific Coast, marine resources probably met some of those nutritional needs as the populations that lived nearby still consumed fish and molluscs, albeit on a smaller scale, considering that agricultural products had already become the significant source of food in this region .…”
Section: Discussionsupporting
confidence: 75%
“…Debido a que la estimación morfológica del sexo en individuos juveniles es problemática, todos fueron clasificados como de sexo indeterminado. * Dataciones 14 C: Cuando se dispuso de más de una datación se mostró la más antigua en años AP, excepto en las indicadas con DC (Filippini 2012;Lima 2000).…”
Section: La Muestraunclassified
“…Cuando la pelvis, las vértebras, las costillas, las clavículas, las escápulas y el esternón estaban presentes, se atribuyó 30% de integridad. En caso de ausencia de uno o varios huesos los porcentajes se rectificaron proporcionalmente (Filippini 2012). "Sin identificación" refiere esqueletos sin origen conocido; "compuesto" es un grupo que contiene esqueletos de varios sitios diferentes encontrados sin contexto.…”
Section: La Muestraunclassified
See 1 more Smart Citation
“…Assim como tantos outros sambaquis, este sítio encontrava-se em rápido processo de destruição, por encontrar-se em área industrial. Foi primeiramente escavado em 1963 por equipe do Museu Paulista, coordenada por Luciana Pallestrini (Pallestrini, 1964a;Garcia, 1970) Mello e Alvim, Vieira, & Cheuiche, 1975;Filippini & Eggers, 2005Okumura, 2007;Fischer, 2012;Filippini, 2012), demográficas (; Mello e Alvim e Uchôa, 1976;Uchôa, Mello e Alvim & Gomes, 1989;Fischer, 2012) e das práticas funerárias (Uchôa, 1973;Silva, 2005) (De Blasis & Piedade, 1991). O sítio…”
Section: Litoral De São Paulo: Histórico Das Pesquisaunclassified